ROLE OF NEUROIMAGING IN METHANOL TOXICITY - A CASE REPORT - Khan, Bushra Muzaffar; Alamgir, Wasim; Fatima, Taqdees (Pakistan Armed Forces Medical Journal, 2019)
Methanol is a frequently used organic solvent. However toxic doses of methanol may lead to serious metabolic acidosis and neurologic side effects including subarachnoid hemorrhage and sometimes even death. The case described suffered from such poisoning. Diagnosis was made on MRI brain that demonstrated bilateral putamen necrosis a neuro-radiological hallmark of methanol toxicity.